Economic Networking as Implied in Property Law: Certain Aspects - Michailovna Belikova, Ksenia (International Journal of Criminology and Sociology, 2022)
The present paper outlines the current stage in the development of traditional approaches in the field of property law and the relevant legislation and practice in Russia. Some results and tendencies of adapting traditional approaches to the realities of the new time are introduced. The author shows a gradual shift from the concept of property form toward the concept of property regime based on the actual move away from the property holders themselves to the rights that such holders enjoy. The present paper highlights the economic reasons for this state of affairs. It has also been revealed that the method of appropriation of information leads to the changes in the area of property defined, given the parties involved, as state property concerns its definition as communal and public. As a result, a property network regime for information has been formed according to the information available in the network (from inaccessible and restricted to commercial or generally accessible). The author explains the reasons for more complicated property relations and evolving ownership rights for both tangible and digital objects. It has been established that the spare potential of property interpretation in terms of its regimes is significant; thus, it requires further analysis. It is worth highlighting those property regimes and forms as mobile and variable. This paper states that the ethical problem of justice that arises in the context of the effectiveness and the possibility of traditional forms of property, especially private property, contributes to the reassignment of property functions that fit property regimes. This paper provides up-to-date scientific information on Russian legislation and the doctrine/research works (books, articles, etc.), as well as other ideas in the relevant field; the paper contributes to the understanding of the practical and legislative gap (or its absence) in Russian and foreign research results and implications.